2018
DOI: 10.1155/2018/2060138
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Analysis of Healthcare System in Lebanon Using Modified Data Envelopment Analysis

Abstract: The inflow of refugees from Syria into Lebanon necessitates a robust and efficient healthcare system in Lebanon to withstand the growing demand for healthcare service. For this purpose, we evaluate the efficiency of healthcare system in Lebanon from 2000 through 2015 by applying a modified data envelopment analysis (DEA) model. We have selected four output variables: life expectancy at birth, maternal mortality ratio, infant mortality rate, and newly infected with HIV and two input variables: total health expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 19 publications
(24 reference statements)
1
42
0
Order By: Relevance
“…Some scholars have evaluated and studied the efficiency of the public health systems in 171 countries worldwide [ 27 ], the organization for economic co-operation and development (OECD) countries [ 28 , 29 ], the low- and middle-income countries [ 30 ], and the Asian countries [ 31 ]. Other scholars have estimated the public health efficiency in Greece [ 32 ], India [ 33 ], Lebanon [ 34 ], México [ 35 ], and Slovakia [ 36 ]. Some scholars have deeply discussed China’s public health efficiency, and respectively calculated and studied the Chinese provincial community health service efficiency [ 37 , 38 , 39 , 40 , 41 , 42 ] and the allocation efficiency of the public health resources in the coastal provinces of China [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have evaluated and studied the efficiency of the public health systems in 171 countries worldwide [ 27 ], the organization for economic co-operation and development (OECD) countries [ 28 , 29 ], the low- and middle-income countries [ 30 ], and the Asian countries [ 31 ]. Other scholars have estimated the public health efficiency in Greece [ 32 ], India [ 33 ], Lebanon [ 34 ], México [ 35 ], and Slovakia [ 36 ]. Some scholars have deeply discussed China’s public health efficiency, and respectively calculated and studied the Chinese provincial community health service efficiency [ 37 , 38 , 39 , 40 , 41 , 42 ] and the allocation efficiency of the public health resources in the coastal provinces of China [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from Lebanon have shown that the age distribution of HL in both genders was found to be bimodal [12]. Lebanon witnessed improvement in the efficiency of its healthcare system from 2000 to 2015 according to a study done by Ibrahim and Daneshvar [16]. This suggests that HL's bimodal distribution in Lebanon can be explained by the advancement of medical diagnostic studies.…”
Section: Discussionmentioning
confidence: 95%
“…Also, the technical efficiency of the health-care system in Lebanon was evaluated during the period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) where it was found that not only increasing expenditure on healthcare is needed to achieve efficiency but also technical and operational improvement must be maintained (Ibrahim and Daneshvar, 2018).…”
Section: Repsmentioning
confidence: 99%